2012
DOI: 10.1002/anie.201204634
|View full text |Cite
|
Sign up to set email alerts
|

Giant Spin‐Orbit Effects on NMR Shifts in Diamagnetic Actinide Complexes: Guiding the Search of Uranium(VI) Hydride Complexes in the Correct Spectral Range

Abstract: Transition-and inner-transition metal hydride complexes are crucial reagents in a great variety of stoichiometric and catalytic transformations, including CÀH bond activation. [1] As hydrogen atoms near heavy-metal centers are difficult to locate by X-ray diffraction, often their prime characterization is by 1 H NMR spectroscopy, sometimes augmented by IR spectroscopy. A significant part of the utility of 1 H NMR spectroscopy in this field arises from the fact that the chemical shifts of metal-bound protons ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
123
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(135 citation statements)
references
References 48 publications
12
123
0
Order By: Relevance
“…Dimer ments, [26] but are small in this case as the molecules are rather far apart (Cu···Cu distance in the solid: 4.9 ). s orb valuesa ta ppropriate points in the space around 1 (at the "virtual" Ca nd Hp ositions of the nearest neighbour) are all less than d = 1ppm.…”
Section: Nucleus Pristinementioning
confidence: 87%
“…Dimer ments, [26] but are small in this case as the molecules are rather far apart (Cu···Cu distance in the solid: 4.9 ). s orb valuesa ta ppropriate points in the space around 1 (at the "virtual" Ca nd Hp ositions of the nearest neighbour) are all less than d = 1ppm.…”
Section: Nucleus Pristinementioning
confidence: 87%
“…In particular, the role of spin-orbit (SO) effectso nligand chemical shifts (a "heavya tom effect on the light-atom shielding", HALA) has been exposed in severals tudies. [1][2][3][4][5][6] Earlier studies suggested that SO shieldings on directly neighboring atoms induced by occupied MOs with s symmetry with respect to the bond between the heavy neighboring atom and that nucleus are generally negative, whereas those induced by p orbitals are positive. [7] Our recent analysiso ftrans ligand effects on 1 Hs hifts in as eries of square-planar Pt II complexes, [1] and ac omparison between 13 C and 14 Ns hifts in square-planar Au III and Pt II complexes by Vicha et al, [4] gave as omewhat more varied picture, whereby seemingly similarb onding arrangements mayg ive rise to either shieldingo rd eshielding SO effectsd epending on the trans ligand or the central metal.A dding the also frequently important paramagneticc ontributions (s p )t ot he shifts further com-plicatest he situation and makes general predictionsw ithout explicitq uantitative calculations more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with density functional theory (DFT), ZORA is widely applied to calculations of NMR parameters. For a small selection of recent applications to a variety of problems in chemistry see, for instance [11][12][13][14][15][16]. A ZORA module for NMR shielding tensors has been part of the Amsterdam Density Functional (ADF) [17] package since 1999 [18,19], followed by an implementation of a module for calculations of indirect nuclear spin-spin coupling (J-coupling) tensors in the year 2000 [20,21].…”
mentioning
confidence: 99%